ANALISA DAN PERANCANGAN SISTEM ABSENSI MAHASISWA STMIK-NH JAMBI BERBASIS ANDROID - Lisdarti, Lisdarti (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2018)
The development of science and technology was so rapid that offers easiness in running activities and work. The presence of this technology is intended to achieve better results in the achievement of the accuracy of the information. Given good information system will provide easy access to various desirable. One such technology is the development of Android, Android is an operating system for smartphones that have Linux-based. Android provides an open platform for developers to create their own applications that have been used by a variety of mobile devices. An android application can also be used to address the problems that exist in the environment STMIK-NH Jambi like attendance system. This application aims to replace the manual attendance system that already exists for the move to the android-based application system. This application will be much more effective and efficient than the old system. The data entered in the form of data subjects, the student data, and the latest student photos. The device used is Android Studio, genymotion, and Java Develpoment Kit. The programming languages in use are Java and database used is SQLite.